Heavy metals accumulation in lichens Parmeliaceae and mahogany bark as an indicator of air and pollution levels in several locations in Bandung City - Putri Nurul Fitriyyah; Taufikurahman (Acta Biochimica Indonesiana)
Background: Lichens and tree bark are well-known biomonitoring tools for accumulating pollutants in their tissues over an extended period.